IMPROVING THE MANAGEMENT MECHANISM OF TOURIST SERVICES IN TRANSPORT (A CASE STUDY OF KASHKADARYA REGION) - Anvarjon Muxtorjonovich Tuychiyev (European Science Publishing, 2025)
This article explores the current state and prospects for improving the management mechanism of tourist services in the transport sector, using the Kashkadarya region of Uzbekistan as a case study. As tourism becomes an increasingly important component of regional economic development, the integration of efficient transport services and infrastructure plays a critical role in enhancing tourist satisfaction and accessibility. The research identifies the specific challenges in the organization, regulation, and modernization of transport services tailored to tourism needs. It also considers the influence of regional characteristics on the implementation of effective management strategies. The paper offers a conceptual framework for optimizing service delivery by emphasizing coordination among tourism operators, transport providers, and local authorities. The findings provide practical recommendations for stakeholders to increase the efficiency, safety, and comfort of tourist transportation services, thereby supporting sustainable tourism growth in the region.
Keywords: Tourist transport services, transport infrastructure, management mechanism, sustainable tourism, service quality, regional development, Kashkadarya, tourism logistics, transport policy, intermodal transport, innovation in transport, tourist mobility, tourism management, regional integration.